Outpatient prescribing pattern for acute bronchitis in primary healthcare settings in China - Mengyuan Fu (Nature Portfolio, 2021)
Abstract Inappropriate prescribing for acute bronchitis in primary healthcare settings (PHSs) is commonly seen worldwide. Here we describe the prescribing patterns and antibiotic use for acute bronchitis in PHSs across China. We conduct a nationwide cross-sectional survey to collect outpatient prescriptions from PHSs in 2017. Patients diagnosed with acute bronchitis without other infections are eligible for this study. Generalized estimating equations are used for analysis. Overall, 10,678 prescriptions for acute bronchitis from 214 institutions are included. The antibiotic prescription rate is 44.5% for total prescriptions, and differs significantly by region and urban/rural status (p < 0.05). Among all single-antibiotic prescriptions, 91.5% are broad-spectrum. Two-thirds of the prescriptions contain medicines for symptom management. The overall guideline compliance rate of acute bronchitis treatment for adults is 31.0%. Prescribing antibiotics, especially broad-spectrum ones, for acute bronchitis is commonly observed in Chinese PHSs. Targeted interventions are urgently needed for Chinese primary clinicians, especially in western rural areas.